The executive branch of the federal government : purpose, process, and people - Duignan, Brian (Britannica Educational Pub., in association with Rosen Educational Services, 2010)
Traces the history of the executive branch of the United States government from its beginnings in the late eighteenth century through the election of President Barack Obama in 2009, examining how it has shaped the powers and functions of the government and American society.